PERANAN BUDAYA DALAM IMPLEMENTASI GOOD CORPORATE GOVERNANCE - CHAIRUMAN ARMIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
This paper uses Hofstede's (1991) organizational cultural dimension to analyze the implementation of good corporate governance. This paper descriptitively examines the research opportunity about the relationship between organization culture, behavior, and good corporate governance